Dearest Letty : the World War II love letters of Sgt. Leland Duvall - DuVall, Leland, 1911-2006 (University of Arkansas Press, 2011)
Leland Duvall was a member of the 85th Cavalry Reconnaissance Squadron from 1942 to 1945. After the war, he pursued a career in journalism and wrote for several Arkansas newspapers, Gazette.